2014
DOI: 10.1159/000357327
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus NS1 Protein Degrades STAT2 by Inducing SOCS1 Expression

Abstract: Objectives: Respiratory syncytial virus (RSV) nonstructural protein NS1 (NS1) has been shown to block interferon (IFN)-inducible antiviral signaling. The suppressor of cytokine signaling (SOCS) gene family could utilize a feedback loop to block the activation of the JAK/STAT signaling pathway, further inhibiting the activation of host type I IFN. We evaluated the role of the SOCS1 and SOCS3 genes in this antiviral mechanism. Material and Methods: A humanized stable NS1 (rich in GC)-expressing plasmid was const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…While a cytokine-mediated signaling pathway can upregulate SOCS1 expression, viral infection can also do so through various mechanisms. For example, upon IAV infection SOCS1 expression is mediated by RIG1 (Pothlichet et al 2008), but if the cells are exposed to the nonstructural protein1 (NS1) of the respiratory syncytial virus (RSV), SOCS1 is upregulated in a RIG1- or TLR3-independent manner (Xu et al 2014). Therefore, it becomes clear that the associated expression of RIG1 and SOCS1 depends on the external stimuli, and in this context, the extracellular Gal1 and Gal3 may play different roles depending of the prior exposure of the cells to viral or bacterial neuraminidase.…”
Section: Resultsmentioning
confidence: 99%
“…While a cytokine-mediated signaling pathway can upregulate SOCS1 expression, viral infection can also do so through various mechanisms. For example, upon IAV infection SOCS1 expression is mediated by RIG1 (Pothlichet et al 2008), but if the cells are exposed to the nonstructural protein1 (NS1) of the respiratory syncytial virus (RSV), SOCS1 is upregulated in a RIG1- or TLR3-independent manner (Xu et al 2014). Therefore, it becomes clear that the associated expression of RIG1 and SOCS1 depends on the external stimuli, and in this context, the extracellular Gal1 and Gal3 may play different roles depending of the prior exposure of the cells to viral or bacterial neuraminidase.…”
Section: Resultsmentioning
confidence: 99%
“…SOCS1 is well known as a strong negative regulatory factor that limits the extent of TLR3 signaling by inhibiting type I IFN signal transduction (Baetz et al, 2004). Furthermore, RSV nonstructural proteins could up-regulate SOCS1 expression independently of the TLR3 and RIG-I signaling pathways, and such upregulation of SOCS1 could be responsible for the inhibition of STAT2 activation (Xu et al, 2014). These studies imply that RSV becomes latent or persistent by subverting the innate antiviral response; however, it is not clear why the persistent viral cells survived under virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…RSV non-structural proteins have been shown to interact with several host nuclear, cytosolic and mitochondrial factors, leading to suppression of the antiviral response, cell cycle regulation, DNA damage repair and culminating in G 0 /G 1 phase cell cycle arrest (Atreya et al, 1998;Bossert et al, 2003;Boyapalle et al, 2012;Elliott et al, 2007;Lo et al, 2005;Munday et al, 2010;Munir et al, 2011;Ren et al, 2011;Schlender et al, 2000;Spann et al, 2004Spann et al, , 2005Wu et al, 2012;Xu et al, 2014). TGF-b expression during RSV infection has been shown to be important for cell cycle inhibition in the G 0 /G 1 phase (Gibbs et al, 2009;McCann & Imani, 2007;Wu et al, 2011) and miR-24 has been shown to be suppressed by TGF-b (Sun et al, 2008), as well as regulate TGF-b precursor processing (Luna et al, 2011).…”
Section: Rsv Ns1 Modulates Tgf-b Expression Via Klf6mentioning
confidence: 99%
“…The virus-host interactions that follow RSV binding are modified and regulated by several RSV proteins, including non-structural and G proteins, which modulate proinflammatory and antiviral cytokine expression by host cells (Atreya et al, 1998;Bossert et al, 2003;Boyapalle et al, 2012;Elliott et al, 2007;Kotelkin et al, 2006;Liesman et al, 2014;Ling et al, 2009;Lo et al, 2005;Moore et al, 2008;Munir et al, 2011;Ren et al, 2011;Schlender et al, 2000;Spann et al, 2004Spann et al, , 2005Wright et al, 2006;Wu et al, 2012;Xu et al, 2014). RSV non-structural proteins inhibit minigenome transcription and viral RNA replication (Atreya et al, 1998), and abrogate the innate host response to infection in part by controlling expression of host cell proteins involved in the cell cycle and replication (Atreya et al, 1998;Liesman et al, 2014;Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation